Interpretation out of Contradiction: A World of Music in the West Indies - Guilbault, Jocelyne (Canadian University Music Review / Revue de musique des universités canadiennes)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 1994)
This paper addresses the researcher's double challenge: to acknowledge and situate contrasting experiences of the same phenomenon and yet to integrate them into a personal rendition of that phenomenon. An examination of the various strategies employed in ethnographic writing, from the copious use of quotations to dialogical or polyphonic writing, shows how contradictory viewpoints have been given more attention in ethnographic literature, as the politics of representation have developed into an important debate in the social sciences. While these various approaches have undeniably allowed more voices to be heard, they have nevertheless left unanswered the problem of interpretation in the case of contested appropriations or contradictory versions of the same phenomenon. The simple fact of integrating various voices in an ethnography does not indeed constitute in an by itself an explanation of what is being said and why.This paper examines possible uses and treatments of diverging voices in ethnographic writing. By way of illustration, I emphasize the great complexity of the responses and interpretations generated by zouk, a mass-distributed popular music from the West Indies, by presenting contrasting voices and viewpoints from the islands of Guadeloupe, Martinique, Domenica, and Haiti. By doing so, I show, on the one hand, how each viewpoint can provide distinct types of knowledge. On the other hand, I argue that while there can be no analysis which can provide final answers to the questions raised by controversial phenomenon such as zouk, not all the points of view should be accorded the same importance.